The Personal Characteristics of an Islamic Counselor in Understanding Identity Crisis for Adolescents: Array - Kushendar Kushendar; Hartika Utami Fitri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2018)
Islamic counselor as a person is a reflection of self-embodied in everyday behavior which harmony with islamic sharia, and for adolescent, a role model or personal modeling is needed. And the problems that become the focus on adolescence is the identity crisis, which is one form of developmental crisis that occurs in a certain age range identity crisis also refers to the dilemma of student problems, in the form of juvenile delinquency or group behavior leading to destructive behavior. By understanding the problem a counselor is deemed able to help adolescents in overcoming the problem and also as a person is one form of reflection of teenagers against their good person or counselor as a role model that is displayed in a personal form such as the ability to be quiet when with others, has the capacity to empathize, and other personal characteristics.